2018
DOI: 10.1093/ajcn/nqy133
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent bolus feeding promotes greater lean growth than continuous feeding in a neonatal piglet model

Abstract: These results suggest that when neonates are fed the same amounts of nutrients as intermittent meals rather than continuously there is greater lean growth. This response can be ascribed, in part, to the pulsatile pattern of amino acids, insulin, or both induced by INT, which enables the responsiveness of anabolic pathways to feeding to be sustained chronically in skeletal muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 61 publications
4
39
4
Order By: Relevance
“…Meal frequency has been studied in humans as well as animal models, and intermittent fasting may result in increased protein synthesis, lower RQ, and reduced fat mass [23,29]. Some…”
Section: Discussionmentioning
confidence: 99%
“…Meal frequency has been studied in humans as well as animal models, and intermittent fasting may result in increased protein synthesis, lower RQ, and reduced fat mass [23,29]. Some…”
Section: Discussionmentioning
confidence: 99%
“…In a neonatal pig model, intermittently fed animals (enteral feeds given every 4 hours over 15 minutes) demonstrated protein synthesis to a greater extent in a sustained manner over 21 days, compared with animals who were continuously fed. [69][70][71][72] Whether this translates to critically ill, adult humans is still a matter of debate. Nevertheless, one small study comparing intermittent feeding versus continuous nasogastric feeding among postoperative patients showed that those fed intermittently had lower resting oxygen consumption on the 4th and 5th postoperative days and attained better nitrogen balance over a 5-day study period than those fed continuously.…”
Section: Evaluating Feeding Methods Through the Lens Of Optimizing Prmentioning
confidence: 99%
“…(26) Earlier investigations reported that MPS could only be stimulated for a limited time in healthy individuals, despite su cient availability of amino acids. (27) In addition, compared to continuous feeding, IF is assumed to have direct potential advantages over gastrointestinal-hormone secretion (21,28) and indirect advantages due to preservation of pancreatic and gallbladder function, (21) elevated insulin secretion (28,29) and improvement of glucose control. (1) However, whether this physiologic hormone pattern translates into molecular muscle anabolism remains unknown.…”
Section: Introductionmentioning
confidence: 99%